Metabolomic and transcriptomic analyses reveal the mechanism of sweet-acidic taste formation during pineapple fruit development - Gao, Yuyao; Yao, Yanli; Chen, Xin; Wu, Jianyang; Wu, Qingsong; Liu, Shenghui; Guo, Anping; Zhang, Xiumei (Frontiers in Plant Science, 2022)
Pineapple (Ananas comosus L.) is the most valuable fruit crop exploiting crassulacean acid metabolism. Sweet-acidic taste presents as major contributors of fruit attributes, but its formation mechanism in pineapple fruit remain elusive. Here, targeted metabolomic and transcriptomic analyses were performed during the fruit developmental stages in two pineapple cultivars (‘Comte de Paris’ and ‘MD-2’) to generate a global view of metabolism and transport pathways involved in sugars and organic acids accumulation. The levels of different sugar and acid components during development revealed that sucrose and citric acid were the predominant sugar and organic acid in the mature fruit of both cultivars. Weighted gene coexpression network analysis (WGCNA) of metabolic phenotypes and gene expression profiling enabled the identification of 23 relevant genes associated with sucrose accumulation and 19 relevant genes associated with citric acid accumulation. The coordinated interaction of the 23 genes correlated with sucrose irreversible hydrolysis, resynthesis, and transport could be responsible for sucrose accumulation in pineapple fruit. In addition, citric acid accumulation might be controlled by the coordinated interaction of the pyruvate-to-acetyl-CoA-to-citrate pathway, gamma-aminobutyric acid pathway, and tonoplast proton pumps in pineapple. These results provide deep insights into the metabolic regulation of sweetness and acidity in pineapple.